Effect of Thickness and Infill Density on Acoustic Performance of 3D Printed Panels made of Natural Fiber Reinforced Composites. Issue 13 (1st December 2022) - Sekar, Vignesh; Eh Noum, Se Yong; Sivanesan, Sivakumar; Putra, Azma; Chin Vui Sheng, Desmond Daniel; Kassim, Dg Hafizah
ABSTRACT: Additive manufacturing (AM) of Natural Fiber-Reinforced Composites through Fused Deposition Modeling is receiving much attention in recent years. AM is very appealing for complex shape structures that can be inconvenient to produce by other methods. In this study, the acoustic panel made from polylactic acid reinforced with wood fiber composite was 3D printed by varying its thickness and infill density. The sound absorption coefficient was measured using an impedance tube. The thin panel with back air gap was found to absorb sound at mid-frequency range resembling the Helmholtz resonator. The absorption performance for the thick panel can be controlled by controlling the infill density of the panel. Customizing the acoustic absorption is therefore possible for panels from biodegradable materials by AM.